Genomic Analysis of a New Estrogen-Degrading Bacterial Strain, Acinetobacter sp. DSSKY-A-001. (2nd June 2019) - Qiu, Qing; Wang, Ping; Kang, Hui; Wang, Yu; Tian, Kejian; Huo, Hongliang
Abstract : In this study, we isolated a new estrogen-degrading bacterium from a soil sample collected near a pharmaceutical factory in Beijing, China. Morphological observations, physiological and biochemical analyses, and sequence analysis showed that the strain was in the genus Acinetobacter, and it was named DSSKY-A-001. The estrogen degradation rate and growth density of strain DSSKY-A-001 were determined by high-performance liquid chromatography and a growth assay using a microplate reader, respectively. The estrogen degradation rate was 76% on the third day and 90% on the sixth day of culture. Three kinds of estrogen metabolism intermediates were detected by high-performance liquid chromatography and mass spectrometry, and the estrogen metabolic pathway and possible estrogen-degrading enzymes were predicted. RT-PCR was used to verify whether the three putative enzymes, catechol 1, 2-dioxygenase, dioxygenase, and 7 α -hydroxysteroid dehydrogenase, were expressed in the strain. The results of the validation were consistent with the predictions that these three enzymes were present and expressed in Acinetobacter DSSKY-A-001. To further understand the estrogen-degrading activity of the strain at the genetic level, we sequenced the genome and performed a functional gene annotation. Through this gene sequence analysis, we identified genes predicted to encode the previously detected enzymes, catechol 1, 2-dioxygenase, dioxygenase, and 7 α -hydroxysteroid dehydrogenase, as well as six other enzymes that may be involved in estrogen degradation. Therefore, a total of nine enzymes related to estrogen degradation were found.